1994
DOI: 10.1093/wbro/9.2.273
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Benefits of Soil Conservation: The Farmers' Viewpoint

Abstract: Most countries in Central America and the Caribbean depend heavily on agriculture; efforts to sustain and improve the sector's productivity are therefore crucial to the region's economic development and to the welfare of its people. Land degradation is thought to pose a severe threat to the sustainability of agricultural production. Yet despite long-standing concern about this threat and dramatic claims of environmental damage, surprisingly little empirical analysis has been done on the causes and severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 21 publications
2
76
0
5
Order By: Relevance
“…Specifically, households who own at least some of the land they farm are 31% more likely to adopt SLM practices than those who do not. This corroborates Lutz et al (1994) and Shultz et al (1997) assertion that land ownership is likely to influence adoption.…”
Section: Probit Model For Sustainable Land Management Technology Adopsupporting
confidence: 88%
“…Specifically, households who own at least some of the land they farm are 31% more likely to adopt SLM practices than those who do not. This corroborates Lutz et al (1994) and Shultz et al (1997) assertion that land ownership is likely to influence adoption.…”
Section: Probit Model For Sustainable Land Management Technology Adopsupporting
confidence: 88%
“…The study by Lutz, Pagiola, and Reiche (1994) found that landownership positively influences the adoption decision. Pender and Kerr (1998) showed negative effects of sales restrictions of land and tenancy on conservation investments.…”
Section: Adoption Modelsmentioning
confidence: 99%
“…This method is likely to overestimate the values of soil nutrients, as it does not establish any connection between soil nutrients and agricultural production. A decrease in nutrients may have little effect on production, especially when other factors, such as rainfall, represent more important production constraints (Bojö 1996;Lutz, Pagiola, and Reiche 1994). 47 Widely cited applications of the replacement cost approach were developed by Stocking (1986) in Zimbabwe and by Stoorvogel and Smaling (1990), who estimated the nutrients budgets of all Sub-Saharan African countries (Bojö 1996).…”
Section: Replacement Cost Approachesmentioning
confidence: 99%
“…Creating conditions to support longer-term sustainability beyond project completion represents a recurring challenge [43] and it is not uncommon for activities and institutions to become inactive ex-post [44,45] or for stakeholders to revert to previously unsustainable practices or to even actively destroy project measures in some cases [46].…”
Section: Temporal Scale Considerationsmentioning
confidence: 99%